PENGARUH DISIPLIN KERJA DAN LOYALITAS KERJA TERHADAP KINERJA KARYAWAN PADA PT. SATRIA GLOBAL PERSADA - Amelia, Wulan; Wasiman, Wasiman (LPPM Universitas Putera Batam, 2023)
The research was conducted to see the influence exerted on employee performance by work discipline and workloyalty at PT. Satria Global Persada. the method in this study used quantitative methods with the SPSS version27 tool in associative (casual) form by distributing questionnaires to obtain data. the population in this study areall employees who work at PT. Satria Global Persada with a sample of 100 respondents. testing the quality ofthe data using the validates test and reliability test, testing the classical assumptions using the normality test,multicollinearity test and heteroscedasticity test and the influence test using multiple linear regression analysisand analysis of the coefficient of determination (R2). then to test the hypothesis using the t test and f test. Theresults of this study indicate that work discipline and work loyalty have an effect of 55.8% on employeeperformance, while the remaining 44.2% are influenced by other variables outside of this study